DEFENSE RESPONSE TRIGGERED BY SCLEROTIUM ROLFSII IN TEA PLANTS - Bhagat, Indramani; Chakraborty, Bishwanath (Ecoprint: An International Journal of Ecology, 2011)
Total phenols and ortho-dihydroxy phenols from healthy and Sclerotium rolfsii inoculated roots of 18 varieties of tea [Camellia sinensis (L.) O. Kuntze] were estimated after 7 days of inoculation. The total phenol contents and ortho-dihydroxy phenols decreased in susceptible varieties and increased in resistant varieties following inoculation with S. rolfsii. Among all the tested varieties, K-1/1 variety showed maximum increase in total phenols and ortho-dihydroxy phenol contents after inoculation with S. rolfsii. Phenylalanine ammonia lyase (PAL) activity was increased after 4 days of inoculation in eighteen tested varieties. Highest increase in PAL activity was seen on tea roots of TV-26 variety. Peroxidase activity was also increased in all the tested varieties and highest increase was noticed in HV-39 variety. The results showed that changes in the levels of phenols and the enzymes like PAL and Peroxidase (POD) form an important part in the resistance mechanism of the tea plants against infections with S. rolfsii. Resistant varities of tea plants might have an inducible system to produce phenolic compounds and activate certain enzymes following infection with the pathogen whereas susceptible varities seem to be suppressive in this aspect. Key words: Resting pathogen; resistance mechanism. DOI: 10.3126/eco.v17i0.4106 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 69-76 Uploaded date: 3 January, 2011